Cytokinin signaling localized in phloem noncell‐autonomously regulates cambial activity during secondary growth of Populus stems. Issue 4 (8th March 2021) - Fu, Xiaokang; Su, Huili; Liu, Shuai; Du, Xuelian; Xu, Changzheng; Luo, Keming
Summary: The regulation of cytokinin on secondary vascular development has been uncovered by modulating cytokinin content. However, it remains unclear how cytokinin enriched in developing secondary phloem regulates cambium activity in poplar. Here, we visualized the gradient distribution of cytokinin with a peak in the secondary phloem of poplar stem via immunohistochemical imaging, and determined the role of phloem‐located cytokinin signaling during wood formation. We generated transgenic poplar harboring cytokinin oxidase/dehydrogenase ( CKX)2, a gene encoding a cytokinin degrading enzyme, driven by the phloem‐specific CLE41b promoter, indicating that the disruption of the cytokinin gradient pattern restricts the cambial activity. The RNA interference‐based knockdown of the histidine kinase ( HK ) genes encoding cytokinin receptors specifically in secondary phloem significantly compromised the division activity of cambial cells, whereas the phloem‐specific expression of a type‐B response regulator (RR) transcription factor stimulated cambial proliferation, providing evidence for the noncell‐autonomous regulation of local cytokinin signaling on the cambial activity. Moreover, the cambium‐specific knockdown of HK s also led to restricted cambial activity, and the defects were aggravated by the reduced cytokinin accumulation. Our results showed that local cytokinin signaling in secondary phloem regulates cambial activity noncell‐autonomously, and coordinately with its local signaling in cambium.